The Role of State Sukuk Instruments and the Central Bank in the Movement of the Indonesian Sharia Stock Index (ISSI). - ABDUL AZIS R (Jurnal Kolaboratif Sains, 2026)
This study analyzes the influence of government sukuk (SBSN) and central bank sukuk (BI Sukuk) on the performance of the Indonesian Sharia Stock Index (ISSI). The rapid development of Islamic financial instruments in Indonesia emphasizes the strategic role of SBSN and BI Sukuk in the Islamic capital market. However, the high volatility of the ISSI and the weak integration of fiscal and monetary policies raise questions about the effectiveness of these instruments. Using a positivistic approach and quantitative methods, this study uses PLS-SEM on monthly data for the 2020–2024 period. The results show that SBSN has a positive and significant effect on the ISSI, reflecting increased investor confidence and strengthening the Islamic stock market. Conversely, BI Sukuk has a negative and insignificant effect, indicating its more dominant role as a monetary instrument to absorb liquidity. The model has high predictive power with a Q² value of 0.826. These findings confirm the effectiveness of SBSN in supporting the Islamic capital market and recommend an evaluation of BI Sukuk policy to strengthen market integration and Islamic investor participation.